Análise dos sistemas comerciais de medição de descargas parciais em hidrogeradores da Eletrobrás Eletronorte - PARDAUIL, Ana Carolina Neves (2018)
The greatest cause of failure on the Hydrogenerators stator windings is its electrical insulation, so it is necessary to find a safe way to oversee and make efficient diagnosis trying to avoid it. The measurement and analysis of partial discharge is one of the most safe, effective and trustworthy methods of doing the monitoring and diagnosis of the state of the winding. Therefore, this work has as its mains objective establish a comparison between those two partial discharge oversee systems used on the Hydroelectric Plant of Tucuruí, both PDA-H and IMA-DP. The case study in question was used as the object of analysis of a hydraulic generator unit of UHE Tucuruí power house 1, aims to elaborate in detail the concepts and fundamentals covering the partial discharges concept, as well as techniques and circuits used for these tests be conducted in an ideal way and providing the signal with lowest permissible noise and interference possible. To prove the effectiveness of the system, data collections in loco, data already collected and the expertise of the Eletrobras Eletronorte validates the diagnostic presented during this work. The results presents the magnitudes, occurrences types and damage severity of the insulation exposed to differences flaws and the contributions that each one has, thereby providing a higher level of information and a more accurate and trustworthy diagnosis of the stator windings electrical insulation.